THE RELATIONSHIP BEHAVIOR OF PREGNANT WOMEN TO THE UTILIZATION OF TRIPLE ELIMINATION EXAMINATION IN PUSKESMAS KUALA BANGKA KAB. LABUHAN BATU UTARA - Nur Azizah; Kismiasih Adethia; Lisa Putri Damanik; Rosmani Sinaga; Diah Pitaloka (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Pregnant women are one of the population at risk of contracting HIV/AIDS, Hepatitis, Syphilis. More than 90% of children are infected with HIV, Syphilis and Hepatitis B from their mothers. The risk of mother-to-child transmission for HIV/AIDS is 20%-45%, for syphilis it is 69-80%, and for hepatitis B it is more than 90% (Ministry of Health, 2017). Infection, syphilis and hepatitis B have the same transmission route, namely through sexual, blood and vertical transmission from mother to child. Infectious diseases such as HIV infection, hepatitis B and syphilis that can be transmitted from mother to fetus through pregnancy, childbirth and breastfeeding, and can cause illness, disability, and death, thus adversely affecting the survival and quality of life of children. However, this can be prevented by simple and effective interventions in the form of early detection (screening) during antenatal care services during a pandemic, namely a minimum of 6 times during pregnancy and services with 10 T and one of the supporting examinations carried out is hemoglobin and triple elimination. Elimination of examinations on every pregnant woman for HIV/AIDS, Hepatitis B and Syphilis which is a form of state responsibility for this problem with the aim of reducing the number of new infections in newborns so that the eyes of transmission from mother to child are cut off. The type of research used is a cross sectional study. This research was a cross sectional analytical survey research. The sample in this study amounted to 35. The sampling technique used in this study used purposive sampling. Results of the study showed that knowledge (p=0.007<0.005), attitude (p=0.45<0.05) and actions (p=0.049<0.05), so it can be concluded that there is a relationship between pregnant women's behavior on the use of triple elimination examination at the Kuala Bangka Health Center, Kab. North Stone Harbor in 2022.